2011
DOI: 10.3109/1354750x.2010.548010
|View full text |Cite
|
Sign up to set email alerts
|

Urinary p-cresol is elevated in small children with severe autism spectrum disorder

Abstract: Several studies have described in autistic patients an overgrowth of unusual gut bacterial strains, able to push the fermentation of tyrosine up to the formation of p-cresol. We compared levels of urinary p-cresol, measured by high-performance liquid chromatography-ultraviolet, in 59 matched case-control pairs. Urinary p-cresol was significantly elevated in autistic children smaller than 8 years of age (p < 0.01), typically females (p < 0.05), and more severely affected regardless of sex (p < 0.05). Urinary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 34 publications
8
124
0
2
Order By: Relevance
“…A recent metabonomic study revealed metabolic phenotype (metabotype) differences were observed between autistic and control children, which were associated with perturbations in the relative patterns of urinary mammalian microbial co-metabolites including dimethylamine, hippurate, and phenyacetylglutamine (Yap et al 2010). Another study by Altieri et al (2011) found higher levels of p-cresol in urine of young children with autism than controls and also reported a positive correlation between urinary p-cresol and autism severity. P-cresol is a toxic metabolite of tyrosine catabolism by gut bacteria such as clostridial species and Pseudomonas stutzeri (Altieri et al 2011).…”
Section: Altered Gut Fermentation Products In Autismmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent metabonomic study revealed metabolic phenotype (metabotype) differences were observed between autistic and control children, which were associated with perturbations in the relative patterns of urinary mammalian microbial co-metabolites including dimethylamine, hippurate, and phenyacetylglutamine (Yap et al 2010). Another study by Altieri et al (2011) found higher levels of p-cresol in urine of young children with autism than controls and also reported a positive correlation between urinary p-cresol and autism severity. P-cresol is a toxic metabolite of tyrosine catabolism by gut bacteria such as clostridial species and Pseudomonas stutzeri (Altieri et al 2011).…”
Section: Altered Gut Fermentation Products In Autismmentioning
confidence: 91%
“…Another study by Altieri et al (2011) found higher levels of p-cresol in urine of young children with autism than controls and also reported a positive correlation between urinary p-cresol and autism severity. P-cresol is a toxic metabolite of tyrosine catabolism by gut bacteria such as clostridial species and Pseudomonas stutzeri (Altieri et al 2011). Whether the observed differences in urinary metabolites observed contribute to, or reflect, GI dysfunction in individuals with ASD requires further investigation.…”
Section: Altered Gut Fermentation Products In Autismmentioning
confidence: 99%
“…Daily systemic administration of 4-EPS to naive mice for three weeks induced in an open-field test an anxiety-like behaviour similar to that observed in the diseased mice. Interestingly, 4-EPS is chemically related to p-cresol (4-methylphenol), an end-product of bacterial tyrosine metabolism, which has been reported to be a possible urinary biomarker for autism (Altieri et al, 2011). The involvement of the autonomic nervous system in the communication between the gut microbiota and the brain was demonstrated by vagotomy experiments.…”
Section: How Does the Gut Microbiota Communicate With The Brain To Inmentioning
confidence: 98%
“…In fact, macrocephaly (i.e., head circumference >97th percentile) has been consistently described in approximately 20% of autistic children [55,58,59], serotonin blood levels are elevated in 20%50% of autistic subjects [47], and increased urinary excretion rates of oligopeptides and multiple solutes is found in 20-60% of autistic patients, with significant interethnic differences [50,60,61]. The implementation of these endophenotypes in our studies is detailed in the following section.…”
Section: Endophenotypes In Autism Genetic Researchmentioning
confidence: 99%
“…of venipuncture to collect 12 mL of supernatant (i.e., platelet-rich plasma), which is immediately frozen in dry ice and stored at 80°C to later measure serotonin blood levels. Urine samples (yellow tubes in Figure 1) are used to study urinary bio-markers, such as p-cresol [61]. In general, it is extremely important for investigators interested in endophenotyping to diversify the collection of biomaterials as much as possible (blood, plasma, serum, urines, hair bulb, saliva, etc.).…”
Section: Our Roadmap: Methodological Issues and Strategiesmentioning
confidence: 99%